INFLAMMABILITE ET TENEUR EN EAU DES COMMUNAUTES VEGETALES A CISTUS DANS LA REGION DE TLEMCEN (NORD-OUEST ALGERIEN) - Henaoui, Smaïn El-Amine; Bouazza, Mohammed; Hassiba, Stanbouli-Meziane (European Scientific Journal, ESJ, 2013)
The study aims to highlight the fragility of Cistus plant formations according to flammability and water content of plant species that colonize. The variation between the flammability and water content is irregular for tested plant taxa which leads us to affirm we can say that during the spring season the water content is not the only factor that affects the flammability of plant species, but it is strongly on the rise of the sensitivity of the latter, plant physiology returned as an element associated with it including the composition of volatile organic compounds to determine the hatching phenomenon of forest fires. The statistical treatment by factor analysis (FA) clearly shows that plant communities based on Cistus of the study area are very vulnerable and susceptible to fire. Finally, according to our results the High degree of flammability and water content characterizes the majority of plant taxa, the prevention and long-term forecasting is an essential step in the fight against forest fires.